Integrasi Nilai-Nilai Keislaman pada Proyek P5 di SDN 7 Pahandut Palangkaraya - Hapipah, Nor; Santosa, Sadya (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
General learning is integrated with Islamic values so that learning becomes meaningful and interesting, students look more enthusiastic about every learning process. The purpose of this study was to find out more about the integration of Islamic values with the implementation of the P5 project at SDN 7 Pahandut Palangka Raya. The research subject in this study was one class teacher. Data collection techniques using interviews. The type of research method uses a qualitative approach to case study research methods. Data analysis techniques are processing data reduction, presentation, conclusion drawing and verification. The results obtained show the integration of Islamic values in P5 in elementary schools that the importance of this connection can be a strategic step so that students not only understand world knowledge but also understand how Islam views an action. The value of Islam is very broad not only regarding mahdhah worship but also social, economic and education issues, Islam is very comprehensive, it starts this Islamic value is perfect if applied in its entirety.